Making space for contending moral talk in criminal matters: Criminal court mediation in Brooklyn, New York. Issue 1 (23rd May 2018) - Miller, Peter; Arms Almengor, Rochelle; Goldberg, Jessica
Abstract : This article describes in detail the rationale behind the evolution of the mediation process used in the Criminal Court Mediation Program in Brooklyn, New York. The process developed as a response to high emotion contentious conflicts in misdemeanour cases that came through the programme, in which defendants unexpectedly insisted on countering complainants' moral assertions about fault and harm. Through the story of one case, characteristic of many that come through the programme, we describe stages of the process from intake through mediation, and highlight key components: separate, pre-mediation sessions; regular opportunities of choice for all parties; and no promises about what will be discussed in mediation, in order to support agency and bilateral moral discourse. The programme's success is evinced by highly positive feedback from both defendants and complainants, including increased feelings of safety. We hope our experience will serve as a reference for programmes receiving similar types of cases.